2018
DOI: 10.1016/s0140-6736(18)31267-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid urine-based screening for tuberculosis in HIV-positive patients admitted to hospital in Africa (STAMP): a pragmatic, multicentre, parallel-group, double-blind, randomised controlled trial

Abstract: SummaryBackgroundCurrent diagnostics for HIV-associated tuberculosis are suboptimal, with missed diagnoses contributing to high hospital mortality and approximately 374 000 annual HIV-positive deaths globally. Urine-based assays have a good diagnostic yield; therefore, we aimed to assess whether urine-based screening in HIV-positive inpatients for tuberculosis improved outcomes.MethodsWe did a pragmatic, multicentre, double-blind, randomised controlled trial in two hospitals in Malawi and South Africa. We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
180
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 26 publications
9
180
1
Order By: Relevance
“…In our setting, TB was also the main co‐infection. This is not surprising, as the national population incidence of TB in South Africa was 774/100 000 persons in 2012 31 and the reported prevalence among HIV‐seropositive inpatients in two large hospitals in the KwaZulu‐Natal and Western Cape provinces was 22% and 32%, respectively 32,33 . In addition, we observed high proportions of prior TB among enrolled patients.…”
Section: Discussionsupporting
confidence: 52%
“…In our setting, TB was also the main co‐infection. This is not surprising, as the national population incidence of TB in South Africa was 774/100 000 persons in 2012 31 and the reported prevalence among HIV‐seropositive inpatients in two large hospitals in the KwaZulu‐Natal and Western Cape provinces was 22% and 32%, respectively 32,33 . In addition, we observed high proportions of prior TB among enrolled patients.…”
Section: Discussionsupporting
confidence: 52%
“…These studies often had dedicated staff to collect spontaneous or induced sputum, and so managed to obtain sputum from a high proportion of patients; such dedicated sputum collection might be unfeasable in routine practice. In a previous study, 29 the addition of urine LAM testing to sputum Xpert reduced mortality in hospital inpatients with HIV with suspected tuberculosis who had a CD4 count of less than 100 cells per µL or severe anaemia, subgroups at highest risk of M tuberculosis BSI.…”
Section: Discussionmentioning
confidence: 93%
“…A recent review showed that urine Xpert MTB/RIF may be helpful in confirming the diagnosis of genitourinary TB (Kohli et al, 2018). Screening using urine Xpert and urine lipoarabinomannan (LAM) increased the identification of TB by 50% among adult hospitalized patients with HIV (Gupta-Wright et al, 2018). The use of urine Xpert in pulmonary TB particularly in children remains limited (WHO, 2013).…”
Section: Discussionmentioning
confidence: 99%